Multiturn simulation of radiative Bhabha scattering in the equivalent photon approximation - Peter Kicsiny; Xavier Buffat; Daniel Schulte; Helmut Burkhardt; Tatiana Pieloni; Mike Seidel (Physical Review Accelerators and Beams)
In this paper, we present a Monte Carlo event generator for radiative Bhabha scattering, based on the method of equivalent photons, and optimized for multiturn tracking simulations in the xsuite framework. We demonstrate the accuracy of the event generator with successful benchmarks of the luminosity and event cross section against currently existing alternative tools. Consequently, we use it to investigate existing estimates of the radiative Bhabha scattering beam lifetime at the FCC-ee, as well as the impact of radiative Bhabha scattering on the beam dynamics, using full nonlinear tracking models.